Modeling sporadic juvenile ALS in iPSC-derived motor neurons explores the pathogenesis of FUSR503fs mutation - Chen, Li; Chen, Guojie; Zhang, Mengting; Zhang, Xiaojie (Frontiers in Cellular Neuroscience, 2024)
Introduction Fused in sarcoma (FUS) mutations represent the most common genetic etiology of juvenile amyotrophic lateral sclerosis (JALS), for which effective treatments are lacking. In a prior report, we identified a novel FUS mutation, c.1509dupA: p. R503fs (FUSR503fs), in a sporadic JALS patient. Methods The physicochemical properties and structure of FUSR503fs protein were analyzed by software: Multi-electrode array (MEA) assay, calcium activity imaging assay and transcriptome analysis were used to explore the pathophysiological mechanism of iPSC derived motor neurons. Results Structural analysis and predictions regarding physical and chemical properties of this mutation suggest that the reduction of phosphorylation and glycosylation sites, along with alterations in the amino acid sequence, may contribute to abnormal FUS accumulation within the cytoplasm and nucleus of induced pluripotent stem cell– derived motor neurons (MNs). Multi-electrode array and calcium activity imaging indicate diminished spontaneous electrical and calcium activity signals in MNs harboring the FUSR503fs mutation. Transcriptomic analysis reveals upregulation of genes associated with viral infection and downregulation of genes involved in neural function maintenance, such as the ATP6V1C2 gene. Treatment with ropinirole marginally mitigates the electrophysiological decline in FUSR503fs MNs, suggesting the utility of this cell model for mechanistic exploration and drug screening. Discussion iPSCs-derived motor neurons from JALS patients are promising tools for drug screening. The pathological changes in motor neurons of FUSR503fs may occur earlier than in other known mutation types that have been reported.